Refining State Level Comparisons in India - Pranjul Bhandari (Planning Commission, Government of India, 2012)
In this paper we analyse the performance of Indian States across three critical sectors – health, education and infrastructure. To enable us to read through multiple indicators of the three sectors, we construct an index for each using the Principal Component Analysis technique. This technique assigns weights according to the relationship between the variables, thus involving relatively low levels of subjectivity on part of the researcher, while preserving most of the information in the original data set. Our ‘raw’ results conform with the already well-established findings of several other studies that states such as Kerala are amongst the best performing while the so-called BIMARU states (Bihar, MP, Rajasthan and UP) are laggards. While this is true on an absolute level, it does not reveal the performance conditional on state level factors. What we do next is refine this analysis. We control our three indices for per capita consumption to put the states on a level playing field and for gauging how well the states have used available resources. Our ‘refined’ analysis throws up rankings which are quite different from the ‘raw’ analysis. For instance, we find clear differentiation between the BIMARU states – while Orissa, Bihar and Chhattisgarh are amongst the best performers, Uttarakhand, Rajasthan and Jharkhand are amongst the worst. While the performance of Himachal Pradesh has been most impressive, Gujarat is amongst the worst on health, Maharashtra on infrastructure, and Haryana on both.